Operations Research Proceedings 2019 : selected papers of the Annual International Conference of the German Operations Research Society (GOR), Dresden, Germany, September 4-6, 2019 /: selected papers of the Annual International Conference of the German Operations Research Society (GOR), Dresden, Germany, September 4-6, 2019. (2020) - Unknown
No abstract available